KEARIFAN MENYIKAPI ANAK USIA DASAR DI ERA GENERASI ALPHA (Ditinjau dari Perspektif Fenomenologi) - Assingkily, Muhammad Shaleh; Putro, Khamim Zarkasih; Sirait, Sangkot (Program Studi PGMI, 2019)
Wisdom is the result of the thoughts, attitudes, and actions of someone who studies philosophy. The period of trantition, ideally should be addressed wisely, including for the alpha generation. This is article aims to examine the wisdom of addressing the phenomenological alpha generation. The formulation of the problem in this research is how wisdom responds to the phenomenological alpha generation according to Edmund Husserl and how to instill a phenomenological attitude for the alpha generation. This research is uses a qualitative approach with the literature study method. The results of this study indicate that (1) alpha generation with all the technological sophistication of its time, responded wisely with efforts to reflect the rights of children, understand childrenfully, inclusive, cooperate with families through open, intentional, and active awareness (2) instilling wise attitudes phenomenologically for the alpha generation is done by stimulating awareness, reduction and transcendental logic, as well as penetrating intersubjective truths.